Effect of water absorption on mechanical properties of sugar palm fibre reinforced sugar palm starch (spf/sps) biocomposites - Sahari, J.; Sapuan, S. M.; Zainudin, E.S.; Maleque, Md. Abdul (American Scientific Publishers, 2012)
A novel biocomposite where both natural fibre and matrix are derived from underutilized parts of sugar palm tree was successfully developed. This 100% green materials can lead to solve depletion and non degradable polymer waste disposal problems. Unfortunately, since moisture absorption is a matter of concern in biocomposites, the effect of water absorption on mechanical properties of sugar palm fibre reinforced sugar palm starch (SPF/SPS) composites has been studied. From this investigation, it can be seen that tensile and impact strengths of biocomposites increase with the increase of fibre content. This enhancement indicates the effectiveness of the SPF to act as reinforcement for composites. But the mechanical properties of the biocomposites dropped after being stored for 72 hours at RH = 75%. In general, the weight gain due to water absorption of all biocomposites linearly increased with the increase of square root of immersion time and it tends to be more constant after a 48 h, following a Fickian diffusion process. Furthermore, moisture absorption decreased with the increase of sugar palm fibre (SPF) content. SEM micrographs showed good dispersion and adhesion between sugar palm starch (SPS) and SPF but large cracks appear on the surface of the matrix (SPS) due to water absorption.